PERSEPSI MAHASISWA AKUNTANSI TERHADAP EFEKTIVITAS E-LEARNING DENGAN FITUR DESAIN - Indriyanti Linting (Paulus Journal of Accounting (PJA), 2023)
This research was motivated by a global situation where the emergence of the Covid-19 virus caused a health crisis. As a result of this situation, the learning system will shift from face-to-face classes to e-learning. The purpose of this study was to determine the perception of students as users about the effectiveness of e-learning with design features. The study was conducted on a total of 295 Hasanuddin University students from class of 2017 to class of 2020 who are still actively studying online. Data were processed using Structural Equation Modeling (SEM) with the AMOS version 20 program. The results showed that perceived usefulness (PU) has a positive effect on the effectiveness of e-learning, while perceived ease (PE) has no positive effect on the effectiveness of e-learning. Testing the design features variable with the Sobel test shows that technology acceptance (PU and PE) has a positive effect on the effectiveness of e-learning. Based on this, Hasanuddin University should prepare better training and introduction to the system. Universities need to use systems with more diverse and simple design features to realize e-learning effectiveness. In addition, e-learning requires positive attitudes and user motivation.